Matahari-shafed wide-band bandpass microwave filter / Muhamad Kamil Khalid - Khalid, Muhamad Kamil (2014)
A novel wide-band bandpass filter is proposed using interconnected identical quarter wavelength coupled lines that form a shape resembling the sun(Matahari). The symmetrical structure is found to be capable of producing very wide bandwidth beyond 80%. In this paper, a total of six half-wavelength resonators were formed by using this topology and a 4th order bandpass response is obtained. The filter is fabricated on FR-4 substrate and measured experimentally to show the feasibility of the concept.